Processo decisório e motivação no âmbito das normas sobre o 'rol de procedimentos e eventos em saúde': uma análise exploratória - Ramalho, Bruno Araujo (2017)
Procedural requirements related to decision making and justification of regulatory choices may have limited application under uncertainty, informational limitation and other obstacles that lead the regulator to adopt strategies to tailor decision making to reality. Based on this hypothesis, and considering the uncertainties and issues of high technical complexity related to the 'list of health care procedures and events in health care', the objective of the research was to carry out an exploratory analysis intended to identify limitations, obstacles and observable strategies in the elaboration and justification of these norms. For this purpose, it was adopt a methodology of qualitative analysis based on documentary research, which included different documents available through the National Regulatory Agency for Private Health Insurance and Plans (ANS) website in public consultations, in the Technical Group for reviewing the list of procedures and in the Committee on Regulation of Health Care (COSAÚDE). As a result, it was verified the hypothesis mentioned above, since the dynamics of the choice presents restrictions that lead the regulator to adopt different strategies to deal with. The obstacles related to 'decision-making' dimension arise from the complexity and uncertainties related to the medical evidences, informational limitations and from interferences of the Legislative Branch and the Judiciary. Regarding the giving reasons requirement, although it is possible to see a greater density of justification starting in 2013, the reasons and replies presented in a synthesized format often do not suffice to clarify all the issues that support complex choices. Among the proposals of the study, the regulator should to provide a more detailed record about the valuation and the operationalization of its methodology criteria.